Polyacrylamide/Polyethyleneimine-Bottom Fly Ash Polymer Gel For Water Shut-Off In Oil Wells - Muhd Aqram Zaki, Manzur (Universiti Sains Malaysia, 2018)
Polyacrylamide (PAM) (1.7-3.6wt%) as the polymer and polyethyleneimine (PEI)(0.18-0.62wt%) as the cross-linker were applied in this study. Investigation conducted includes on the performance of the pure polymer gel based on different formulations, performance optimization by incorporation of inorganic solid micro particles (0.3-0.92wt% ) which were the Bottom Fly Ash and the Boiler Fly Ash into the selected pure polymer gel matrix, and the behaviour of the optimized polymer gel at elevated temperatures beyond 90℃. In this study, the performance of polymer gel were mainly measured in terms of the gelation time. For the pure polymer gel formulation, the study involves the manipulation of PAM concentration and PEI concentration where both experiment was conducted at 90℃. It was found that, with the increase of either PAM or PEI concentration, the gelation time of polymer gel tend to decrease. 2.8wt% PAM with 0.37wt% PEI polymer gel was chosen for further optimization. Based on the two different fly ash incorporated at 90℃, Bottom Fly Ash exhibits a better performing polymer gel in terms of the gelation time. The optimum gelation time were obtained when 0.3wt% were incorporated into the pure polymer gel matrix. Thirdly, for the optimum polymer gel study at elevated temperatures which were 105℃ and 120℃, it was found that the gelation time tend to decrease with the increase of temperature. However, at 120℃, the polymer gel tend experience volume reduction which shows this respective formulated polymer gel are limited to function below 120℃. Besides that, verification on the optimized gel permeability towards oil and brine water also were conducted to ensure the success of the water shut-off agent itself. Results shows that no penetration of either oil or brine water into the polymer matrix and this represents the water shut-off agent formulated is a success.